Economic Analysis of Different Coronary Syndrome Treatment Strategies in a Prehospital Setting - Nam, Julian (My University, 2013)
BACKGROUND
For ST-segment elevation myocardial infarction (STEMI) patients received by emergency medical services (EMS), prehospital identification with 12-lead electrocardiogram/cardiography (ECG) and advanced notification of the receiving centre may increase access to primary reperfusion and reduce mortality, compared to standard cardiac monitoring. The lifetime benefits and costs of upgrading to a 12-lead ECG system are uncertain.
OBJECTIVE
To determine the cost-effectiveness of prehospital identification with 12-lead ECG and advanced notification vs. no prehospital identification and no advanced notification.
METHODS
A probabilistic Markov model was designed from a government payer perspective. Outcomes were lifetime incremental quality-adjusted life-years (QALYs) and healthcare costs. Type of primary reperfusion, 30-day and one-year mortality were from a cohort study conducted in Ontario. Reinfarction, stroke and revascularization rates were derived from the literature. Inpatient costs and professional fees came from the Ontario government; follow-up costs from published literature. The analysis was stratified by eligibility to bypass to a percutaneous coronary intervention (PCI) centre.
RESULTS
In bypass eligible settings, prehospital identification and advanced notification led to an average 0.23 additional QALYs and $1,501 additional costs over no prehospital identification and no advanced notification. In bypass ineligible settings, it led to an average 0.15 fewer QALYs and $130 additional costs. It was a cost-effective strategy 87% and 40% of the time in bypass eligible and ineligible settings, respectively, at a willingness-to-pay of $50,000/QALY.
CONCLUSIONS
In bypass eligible settings, prehospital identification with 12-lead ECG and advanced notification is a cost-effective intervention. In bypass ineligible settings, there is no evidence of cost-effectiveness.
Keywords: STEMI; prehospital; 12-lead ECG; cost-effectiveness; economics; Health Economics; Health Economics